Is the "Earth-ionosphere capacitor" a valid component in the atmospheric global electric circuit?. (November 2017) - Haldoupis, Christos; Rycroft, Michael; Williams, Earle; Price, Colin
Abstract: This paper examines whether the Earth-ionosphere capacitor (EIC) model is correct, by comparing observed atmospheric electrical properties with those expected for a spherical capacitor, as defined in electrostatics. The comparisons suggest that the EIC concept cannot be reconciled with, and hence cannot account for, the observations, particularly the rapid reduction of the atmospheric electric field with height that is measured. This means that the spherical EIC concept is incorrect by being too simplistic; it is thus misleading. The reason for this flawed concept is simple: the model disregards the non-uniform conductivity of the atmosphere which requires the presence of a net positive charge in the lower atmosphere that equals in magnitude the Earth's negative charge. This positive charge shields the action of the Earth's negative charge from polarizing the ionosphere positively. Thus, the lower D region ionosphere remains electrically neutral, which makes the EIC concept inappropriate. Highlights: The Earth-ionosphere (EIC) capacitor concept is widely known and has been used in atmospheric electricity for a long time. The EIC model cannot adequately account for key observations in atmospheric electricity; therefore it is inapplicable. The EIC model fails because it disregards the increase of conductivity with height and hence the net charge in the atmosphere.